Expanding the non-technical skills vocabulary of operating room nurses: a qualitative study - Irene Sirevåg; Ingrid Tjoflåt; Britt Sætre Hansen (BMC, 2023)
Abstract Background Operating room nurses have specialised technical and non-technical skills and are essential members of the surgical team. The profession's dependency of tacit knowledge has made their non-technical skills difficult to access for researchers, thus, creating limitations in the identification of the non-technical skills of operating room nurses. Non-technical skills are categorised in the crew resource management framework, and previously, non-technical skills of operating room nurses have been identified within the scope of the framework. The purpose of this study is to explore operating room nurses' descriptions of their practices in search for non-technical skills not included in the crew resource management framework. Methods This study has a qualitative design. An expert panel of experienced operating room nurses (N = 96) in Norway provided qualitative descriptions of their practice in a Delphi survey. The data were analysed in an inductive thematic analysis. This study was conducted and reported in line with Standards for Reporting Qualitative Research (SRQR). Results The inductive thematic analysis developed two themes, 'Ethical competence' and 'Professional accountability', that encompass operating room nurses' novel descriptions of their non-technical skills. The participants take pride in having the patients' best interest as their main objective even if this may threaten their position in the team. Conclusions This study has identified novel non-technical skills that are not described in the crew resource management framework. These findings will contribute to the development of a new behavioural marker system for the non-technical skills of operating room nurses. This system will facilitate verbalisation of tacit knowledge and contribute to an increased knowledge about the operating room nursing profession.